Image Segmentation Based on New Modification on Normalized-Cut Algorithm - Khalil Alsaif (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, Normalized Cut algorithm was studied to segments any type of digital images which was widely used recently. In this paper wavelet transformation, and high-high frequency components which hold the edges of the image will be used to replace classical high frequency filters of  the old techniques achieved by the normalized cut algorithm ( which  used CANNY filter for edge detection). When the new modification of the  proposed algorithm applied on the different type of digital images (medical, aerial and natural images) after crossover the CANNY filter by the wavelet high-high coefficients, a very efficient segments were found much better than the segments got before, in addition to a deep information can be seen if the selected  segment is projected on the original image to be recognized.